2015
DOI: 10.5414/cp202457
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled repeat-dose thorough QT study of inhaled loxapine in healthy volunteers

Abstract: Objective: This randomized, double-blind, active- and placebo-controlled, crossover, thorough QT study assessed the effect of two inhaled loxapine doses on cardiac repolarization as measured by corrected QT (QTc) interval in healthy subjects (ClinicalTrials.gov NCT01854710). Methods: Subjects received two doses of inhaled loxapine (10 mg) 2 hours apart + oral placebo, two doses of inhaled placebo + oral placebo, or two doses of inhaled placebo + oral moxifloxacin (400 mg; positive control), with ≥ 3 days washo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Another great advantage of inhaled loxapine is the lack of the effect on cardiac repolarization. In fact, Cassella et al [ 48 ] showed that two therapeutic doses of inhaled loxapine did not cause threshold QTc prolongation, thus confirming the previous results of Spyker et al [ 47 ], who demonstrated that there was no apparent QT prolongation associated with the therapeutic dose of inhaled loxapine. Also, in clinical studies of agitated patients with psychiatric disorders, inhaled loxapine did not cause QTc prolongation or torsade de pointes [ 49 , 52 , 53 , 54 , 55 ].…”
Section: A Clinical Perspective On the Role Of Inhaled Loxapine Insupporting
confidence: 69%
See 3 more Smart Citations
“…Another great advantage of inhaled loxapine is the lack of the effect on cardiac repolarization. In fact, Cassella et al [ 48 ] showed that two therapeutic doses of inhaled loxapine did not cause threshold QTc prolongation, thus confirming the previous results of Spyker et al [ 47 ], who demonstrated that there was no apparent QT prolongation associated with the therapeutic dose of inhaled loxapine. Also, in clinical studies of agitated patients with psychiatric disorders, inhaled loxapine did not cause QTc prolongation or torsade de pointes [ 49 , 52 , 53 , 54 , 55 ].…”
Section: A Clinical Perspective On the Role Of Inhaled Loxapine Insupporting
confidence: 69%
“…Several studies on healthy volunteers have been conducted in order to assess the pharmacokinetics and tolerability of inhaled loxapine [ 46 , 47 , 48 , 49 , 50 ] ( Table 2 ). The administration of inhaled loxapine results in a rapid absorption, with a Tmax of two minutes, reaching a mean maximum plasma concentration ( C max) of 257 ± 219 ng/mL [ 26 , 29 ].…”
Section: Overview Of Inhaled Loxapinementioning
confidence: 99%
See 2 more Smart Citations
“…EPS, including akathisia, were uncommon and statistically non-significant when compared to placebo, unlike what can be seen with intramuscular haloperidol 37. Inhaled loxapine does not prolong the QTc interval 21,28,40…”
Section: Inhaled Medications: Loxapinementioning
confidence: 99%